Pengaruh Perbedaan Status Pegawai Terhadap Kinerja Pegawai di Kantor Kesejahteraan Rakyat Kabupaten Mandailing Natal - Desi Rani; Sudarman Sudarman (Universitas Teuku Umar, 2021)
The current 4.0 revolution requires all lines to continue to transform in providing excellent service to the community. This is due to the development of science and increasingly sophisticated technology. Competition between fields is getting more challenging, including the government, highly highlighted for public consumption. All must be able to maintain the existence of their institutions to survive in the current 4.0 era. The purpose of this study was to examine the effect of differences in employee status on employee performance at the Office of the People's Welfare of Mandailing Natal Regency. This study is a quantitative study with a research population of fewer than 100 people, so all 30 employees were used as research samples. The data analysis technique used is a simple linear regression (t) test. After statistical tests were carried out, it was obtained that the employment status had a positive regression coefficient value of 36,053. The results of this positive coefficient value indicate that employment status has a positive effect on employee performance. All statements of employment status and performance variables have a value of 0.33, meaning that the performance indicators, namely, work quality, quantity, timeliness, effectiveness, and independence, are all good. Employees who have higher employment status will have better performance in service compared to non-status employees.